Study of the habitat, and potential distribution of Himalayan Ginseng (Panax pseudoginseng Wall.), and the diversity of its associated species in Nangkor and Shingkhar Geogs, Zhemgang, Bhutan - Dendup, Tashi; Rai, Sushila (International Journal of Environment, 2022)
Panax pseudoginseng Wall. is a highly sought-after medicinal plant in Bhutan, but little is known about its distribution and habitat in the country. Therefore, this study aimed to determine suitable habitat, and potential distribution of P. pseudoginseng, and the diversity of its associated species in Nangkor and Shingkhar Geogs, Zhemgang, Bhutan. A total of 42 plots were laid using a purposive sampling method. Various parameters like slope, aspect, soil nutrients, soil pH, humidity, temperature, and soil water tension were collected. The Spearman’s correlation test indicated that the temperature and canopy cover had negative association with the counts of P. pseudoginseng. The Spearman's correlation test for NPK indicated that Phosphorus had significant difference with the counts of P. pseudoginseng. A total of 1,277 species distributed in 87 genera of 66 families were recorded including the trees, herbs and pteridophytes. Fagaceae was the most dominant family in the study area. Seven types of forest were classified based on the floristic composition of trees.  Potential distribution was obtained using ArcGIS that combined observation data, reclassification and Weighted Overlay. Overall, 95.39% of an area under Zhemgang District is suitable for the growth of P. pseudoginseng.